DESIGN HOTEL FRONT OFFICE COMPUTERIZED SYSTEM (FRONT OFFICE) - Sri Dinar Miyati; Ir. Irwan Nimara (Jurnal Sistem Informasi, 1996)
Hotel front office system design is very helpful in terms of service to the guests. Thiscould be the author see the work on improving the quality of the employeesdemanded accuracy in their respective fields, especially the hotel front officeemployees. In this case the computerization of the most important is a goodalternative in the implementation of the system and its control. The results obtained inthe form of efficiency and all work can be done properly with the help of computersso that all work can be carried out carefully for the betterment of the hotel.